PENINGKATAN KOMPETENSI PEDAGOGIK GURU SD MELALUI WORKSHOP TRANSFORMASI PEMBELAJARAN MENDALAM - Shofiya Amini; Dewi Maisyafarotul Amelia; Andayani Purnamasari; Bahri Nurul Hidayat; Aulil Ardiansyah; Moh. Rosuli; Ali Armadi; Vien Arifiah; Didik Darmadi (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to analyze the improvement of elementary school teachers’ pedagogical competence through a deep learning-based instructional transformation workshop conducted at SDN Dependa 1, in response to the demands of 21st-century education that emphasize meaningful and student-centered learning. This research employed a qualitative approach with a case study design, involving the school principal and teachers selected through purposive sampling. Data were collected through in-depth interviews, participatory observation, and documentation, and analyzed using the Miles and Huberman interactive model, with validity ensured through triangulation and member checking. The findings reveal that the workshop had a positive impact on enhancing teachers’ pedagogical competence, as indicated by improved understanding of deep learning concepts, the ability to design student-centered lesson plans, enhanced classroom management skills, and increased capacity for reflective practice and instructional material development. These improvements also contributed to greater student participation and better conceptual understanding. Therefore, the deep learning transformation workshop is proven to be effective in promoting sustainable changes in teaching practices and improving teachers’ pedagogical competence. It is recommended that such workshops be accompanied by continuous mentoring and replicated in other schools to support broader educational transformation.